2001
DOI: 10.1007/s11746-001-0385-x
|View full text |Cite
|
Sign up to set email alerts
|

Deterpenation of Brazilian orange peel oil by vacuum distillation

Abstract: The deterpenation of orange peel oil in most industries is accomplished by vacuum distillation, but surprisingly little information on this matter can be found in the open literature. This work reports recent results on orange peel oil deterpenation carried out in an automatic vacuum distillation column operated in the semibatch mode at the temperatures of 50, 65, and 80°C, at 10, 20, and 30 mbar, and with reflux ratios of 0.25, 0.50, and 0.75. The concentrates were analyzed with regard to the oxygenate compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 3 publications
0
24
0
5
Order By: Relevance
“…The alcohol β-bisabolol was found in lime for the first time in the year 2004 (Yadav et al, 2004); in this study, it was found with a concentration that was 50% higher. There were no reported values for the content of nonanal and undecanal; these aliphatic aldehydes are related to the quality of citrus (Stuart et al, 2001) and have aromatic properties, first described as having citrus-like and soapy notes (Berger, 2007). Other compounds, such as aromadendrene and camphene, are not reported; camphene has a role in the digestion of fat through increasing bile secretion (Berger, 2007).…”
Section: Chromatographic Analysismentioning
confidence: 99%
“…The alcohol β-bisabolol was found in lime for the first time in the year 2004 (Yadav et al, 2004); in this study, it was found with a concentration that was 50% higher. There were no reported values for the content of nonanal and undecanal; these aliphatic aldehydes are related to the quality of citrus (Stuart et al, 2001) and have aromatic properties, first described as having citrus-like and soapy notes (Berger, 2007). Other compounds, such as aromadendrene and camphene, are not reported; camphene has a role in the digestion of fat through increasing bile secretion (Berger, 2007).…”
Section: Chromatographic Analysismentioning
confidence: 99%
“…The ability of the ionic liquid to extract the linalool from the essential oil mixture was evaluated from the experimental data at the three different temperatures using the solute distribution ratio, LiOH , and the selectivity, S, parameters: (6) where x represents the mole fraction of each component. Values close to one were obtained for the solute distribution ratio which are presented in Table 2.…”
Section: Solvent Evaluationmentioning
confidence: 99%
“…Selective elimination of terpenes is called deterpenation. There are different methods to deterpenate essential oils as, extraction with supercritical fluids [2], membrane based separation technologies [3], liquid-liquid extraction [4], microwave extraction with ionic liquids as the absorption medium [5] and the most common one, vacuum distillation [6]. Sometimes, the essential oil components are too sensible to high temperatures and can be denatured causing undesirable effects in its properties.…”
Section: Introductionmentioning
confidence: 99%
“…This oil comprises highly volatile and nonvolatile components like terpene, oxygenated hydrocarbons, pigments and waxes. The oxygenated parts which include alcohols, aldehydes and ketones contribute more towards flavouring as compared to the terpenes (Stuart et al 2001). Orange peel oil was encapsulated with maltodextrin and mesquite gum mixtures used in 1:4, 2:3, 3:2 and 4:1 (w/w) ratios in solution (30%).…”
Section: Flavoursmentioning
confidence: 99%